Recent progress on hierarchical MoS2 nanostructures for electrochemical energy storage. Issue 12 (4th March 2022) - Jia, Yulong; Yin, Guoliang; Lin, Yinhe; Ma, Ying
Abstract : This review demonstrates the recent progress and future research prospect of hierarchical MoS2 nanostructures for electrochemical energy storage. Abstract : Hierarchical MoS2 nanostructures are of increasing importance in energy storage via batteries or supercapacitors. Herein, the various hierarchical MoS2 materials used as electrochemical electrodes are reviewed in detail by classifying the MoS2 into free-standing and substrate-supported hierarchical structures. The growth methods, morphologies, surface area, and electrochemical performance of the hierarchical MoS2 structures, including nanospheres, nanotubes, and nanoboxes are highlighted. Ascribed to the porous features and interconnected nanosheets, the hierarchical architectures demonstrated a large surface area and high structural stability, resulting in a high rate capacity and long cycling life. Based on the spotlight of applications for electrochemical energy storage, the recent progress of hierarchical MoS2 with efficient electrochemical properties is reviewed. Moreover, further research prospects and challenges of hierarchical MoS2 in energy storage are proposed.